Revisiting caspases in sepsis - Aziz, M (Nature Publishing Group, 2014)
Sepsis is a life-threatening illness that occurs due to an abnormal host immune network which extends through the initial widespread and overwhelming inflammation, and culminates at the late stage of immunosupression. Recently, interest has been shifted toward therapies aimed at reversing the accompanying periods of immune suppression. Studies in experimental animals and critically ill patients have demonstrated that increased apoptosis of lymphoid organs and some parenchymal tissues contributes to this immune suppression, anergy and organ dysfunction. Immediate to the discoveries of the intracellular proteases, caspases for the induction of apoptosis and inflammation, and their striking roles in sepsis have been focused elaborately in a number of original and review articles. Here we revisited the different aspects of caspases in terms of apoptosis, pyroptosis, necroptosis and inflammation and focused their links in sepsis by reviewing several recent findings. In addition, we have documented striking perspectives which not only rewrite the pathophysiology, but also modernize our understanding for developing novel therapeutics against sepsis.